Computational Characterization of Astrophysical Species: The Case of Noble Gas Hydride Cations - Montes de Oca-Estévez, María Judit; Prosmiti, Rita (Frontiers in Chemistry, 2021)
Theoretical-computational studies together with recent astronomical observations have shown that under extreme conditions in the interstellar medium (ISM), complexes of noble gases may be formed. Such observations have generated a wide range of possibilities. In order to identify new species containing such atoms, the present study gathers spectroscopic data for noble gas hydride cations, NgH+ (Ng= He, Ne, Ar) from high-level ab initio quantum chemistry computations, aiming to contribute in understanding the chemical bonding and electron-sharing in these systems.The interaction potentials are obtained from CCSD(T)/CBS and MRCI+Q calculations using large basis sets, and then employed to compute vibrational levels and molecular spectroscopic constants for all known stable isotopologues of ground state NgH+ cations. Comparisons with previously reported values available are discussed, indicating that the present data could serve as a benchmark for future studies on these systems and on higher-order cationic rare-gas hydrides of astrophysical interest.